Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia (SDM) terhadap Kapasitas Organisasi - Suci Ananda Sitompul; Nurullaeli Uswatun Hasanah; Lestari Sitorus; Rifayani Rifayani; Firman Firman (Pusat Riset dan Inovasi Nasional, 2025)
Training and development of human resources (HR) is an important aspect in improving organizational capability. Organizational capacity is the power of an institution to achieve strategic goals through the proper utilization of available resources. This research aims to examine the extent to which HR training and development affect organizational capacity building. The method used is a literature review with a qualitative approach, studying various relevant previous studies. The results of the analysis show that HR training and development make a significant positive contribution to organizational capacity building in both the public and private sectors. The findings highlight the importance of continuous investment in training and development programs to improve organizational competitiveness and efficiency.